2016
DOI: 10.18865/ed.26.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Outcomes of New Onset Supraventricular Arrhythmias in African American Patients with Severe Sepsis

Abstract: hospital mortality. However, after multiple adjustments, new onset SVA did not remain an independent predictor of mortality. Ethn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Thirty-six studies reported on the incidence of AF (Table 2). 16, 17, 2255 One study was published in Hebrew, while all others were in English. Twenty-three studies evaluated patients in an ICU, and 13 studies evaluated patients in a hospital ward setting.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six studies reported on the incidence of AF (Table 2). 16, 17, 2255 One study was published in Hebrew, while all others were in English. Twenty-three studies evaluated patients in an ICU, and 13 studies evaluated patients in a hospital ward setting.…”
Section: Resultsmentioning
confidence: 99%
“…46 Regarding other classical risk factors for AF 47 like diabetes, hypertension, obesity, and cardiovascular disease, 11 studies showed that some of those were associated with new-onset AF in sepsis. [23][24][25][26][27]29,[41][42][43][44][45] However in five studies these classical risk factors were not related with new-onset AF, 20,28,29,40,48 thus underlining that new-onset AF in patients with septic syndromes may also be initiated by elevated levels of pro-inflammatory cytokines by activation of the catecholaminergic system, electrolyte alterations, and alteration in volume status during sepsis. 8, 38,39 Regarding echocardiographic findings, Ferrera et al 26 and Liu et al 25 reported that left atrial dimension was larger in patients with new-onset AF than in those who remained in SR. Conversely, in the study of Guenancia et al, 40 there were no differences in left atrial dimension among patients with new-onset AF and those with SR, although new-onset AF patients had a lower left ventricular ejection fraction than patients in SR. 40 Wetterslev et al 49 used three categories to classify the risk factors for development of new-onset AF in adult critically ill patients: (1) predisposing factors, (2) condition-related precipitating factors, and (3) treatment-related precipitating factors.…”
Section: Physiopathology and Risk Factors For New-onset Atrial Fibrilmentioning
confidence: 93%
“…In-hospital mortality in patients with new-onset AF and sepsis was described in 16 studies. In 10 studies, in-hospital mortality was higher in patients with new-onset AF than in patients with SR. 20,[22][23][24][25][26][27][28][29]43 In four studies, 40,44,48,50 the overall ICU-and inhospital mortality rates were similar between patients with and without new-onset AF and two studies were performed in survivors after sepsis. 41,45 Estimated odds ratio (OR) ranged from 1.9 (95% confidence interval [CI], 1.01-4.11) to 5.7 (95% CI, 3.8-8.6) for in-hospital mortality.…”
Section: Morbidity and Mortalitymentioning
confidence: 97%
See 2 more Smart Citations